Engineered nanofiber scaffolds prime chromatin reorganization to sensitize cells for long-term and low-dose chemical hazard detection - Zhang, Yupeng; Zhao, Hang; Jiang, Li; Zhang, Qi; Cao, Tingbao; Wang, Zesheng; Song, Yang; Qu, Kunpeng (Frontiers in Pharmacology, 2025)
Fast and early detection of low-dose chemical toxicity is a critical unmet need in toxicology and human health, as conventional 2D culture models often fail to capture subtle cellular responses induced by sub-toxic exposures. Here, we present a bioengineered three-dimensional (3D) electrospun nanofibrous scaffold composed of polycaprolactone that enhances chromatin accessibility and primes fibroblasts for improved sensitivity to low-dose chemical stimuli in a short period. The scaffold mimics the extracellular matrix, providing topographical cues that reduce cytoskeletal tension and promote nuclear deformation, thereby increasing chromatin openness. Chromatin compaction indices and accessibility assays confirmed significantly more relaxed chromatin in cells cultured on the scaffold compared to those on glass slides. Mechanistic investigations revealed that this chromatin priming effect was mediated by reduced F-actin polymerization and increased nuclear height. To evaluate functional consequences, fibroblasts were challenged with 0.1% paraformaldehyde (PFA), a commonly encountered chemical with known long-term health risks. While cells on 2D substrates showed no significant response, those on the 3D scaffold exhibited early decreases in viability and elevated ROS levels. Prolonged low-dose PFA exposure further confirmed that scaffold-cultured cells could detect cytotoxicity several days earlier than conventional controls. To facilitate clinical translation, we developed a 96-well-compatible platform by plasma-bonding scaffold-coated PDMS sheets with a custom 3D-printed well plate. Optimization of electrospinning time and cell seeding density identified conditions that maximized sensitivity and reproducibility. Then a low-dose ethanol model was developed to conclude that low-dose ethanol can affect cell viability. Together, these findings support a mechanistic model in which increased chromatin accessibility elevates the basal cellular state, expanding the “sensitive window” for detecting physical and chemical insults. This study establishes a robust and scalable platform for fast and early-phase chemical risk screening and offers a novel strategy for modulating cellular responsiveness via mechano-epigenetic regulation. The platform is broadly applicable in toxicology, pharmacology, and environmental health, offering a significant advancement in cell-based biosensing and precision diagnostics.